THE EFFECT OF DETERMINANTS OF HEALTH EXPENDITURES ON HEALTH EXPENDITURES: OECD COUNTRIES PANEL REGRESSION ANALYSIS (Third Sector Social Economic Review, 2022)
Health expenditures and the factors that affect health expenditures are one of the most important issues discussed today. The aim of the study is to examine the effects of GDP, domestic general government health expenditure (% of current health expenditure), pharmaceutical spending per capita, physicians (per 1,000 people), population ages 65 and above (% of total population), fertility rate and urban population rate (all of which are discussed in the literature that they have effects on health expenditure dimensions) on general health expenditure, public health expenditure, and private health expenditure. In the study, panel regression analysis was applied as the method and the 2005-2017 period of OECD member countries was utilized as the data set. According to the panel regression analysis results of the research, it was determined that the GDP, population ages 65 and above, and the pharmaceutical spending had a positive and significant effect on the general health expenditure. It was determined that GDP, domestic general government health expenditure (% of current health expenditure), number of physicians, population ages 65 and above, and pharmaceutical spending have a positive and significant effect on public health expenditure. It was established that GDP, number of physicians, population ages 65 and above have a positive effect, and domestic general government health expenditure (% of current health expenditure) has a negative effect on private health expenditure.
Keywords: General Health Expenditure; Public Health Expenditure; Private Health Expenditure; GDP; Health Indicators